Penyebab Pneumonia pada Balita di Provinsi Sumatera Barat - nurhayati nurhayati; Oktavianis Oktavianis; Fivie Bestrina; Mila Sari (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2021)
Pneumonia toddlers is a contagious disease that are commonly found in West Sumatera Province. The purpose of this study is to determine causes of Pneumoniain Toddlers in the. The type of this study is analytic by using Spear Correlation with a non-reactive approach. The population is all sub-districts in West Sumatra Province; the samples are Pneumonia patient in toddlers in 80 sub-districts of 7 districts / cities. The results of the study shows that there is a correlation between population density (p = 0,000), exclusive breastfeeding (p = 0,000), immunization status (p = 0,000), healthy house (p = 0,000) and nutrition status (p = 0.018) toward Pneumoniain toddler in West Sumatra Province. But, there is no correlation between clean and healthy life behavior toward pneumonia.